INSTITUTIONAL OWNERSHIP, FINANCIAL PERFORMANCE AND FIRM VALUE MODERATED BY CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (Study on Manufacturing Industry Listed at IDX) - Abshor Marantika (Indonesian Journal of Economics and Business, 2012)
The investors want the firm manager to have achievement to maximize the Firm value. Effect The Firm value can reveal the prosperity of company owners. Firm Value can describe welfare the owners. Corporate must be oriented to the benefit (profit) and social aspects (non-profit). Besides making a profit, the company must also contribute to the community that is improving the quality of community life and the environment. This research has some purposes: to test effect Institutional Ownership on Firm Value; to test effect of Financial Performance on Firm Value; to test effect Institutional Ownership on Firm Value moderated Corporate Social responsibility Disclosure; to test effect Financial Perormance on Firm Value moderated Corporate Social responsibility DisclosureThe population of this research is the entire manufacturing industry, which are listed in Indonesian Stock Exchange on the year 2007-2010 with number 147 firms. The sampling technique used is purposive sampling with matched criteria toward research needs. From the criteria, it was obtained 46 firms as sample. Data analysis method used is statistical analysis and econometric analysis with Multple Regression Model and Moderating Regression Analysis (MRA)The research results obtained that: the First, Institutional Ownership is not proven positively effect on Firm Value. This indicates that the Institution Ownership has not been able to increase investor confidence in the corporate of volume and stock prices. Second, Financial Performance proved a positively effect on Firm Value. This is in line with the essential purpose of the establishment of an enterprise, namely to maximize shareholder welfare by increasing the value of the Corporate. Third, Institutional Ownership proven positively effect on Firm Value moderated by Corporate Social Responsibility Disclosure. This suggests that the assessment of Institutional Ownership investors will have a positive effect if the company is also considering the social aspects of the company. Institutional Ownership is not used alone in the consideration of measuring the success of the company in achieving the Firm Value, but the necessary attention to social aspects. Fourth, Financial Performance proved to be positively effect on Firm Value moderated by Corporate Social Responsibility Disclosure. This suggests that Financial Performance is not the only factor determining the success of a Corporate. Financial Performance will be even better if it is supported by the social aspects of the Corporate.